مسؤولية المسيرين عن إفلاس الشركات التجارية - سعاد مبروكي (My University, 2021)
Abstract : Through what was previously studied within the subject of the memorandum, we conclude that the manager who runs the commercial company, especially the money company, such as the limited liability company and the joint stock company. Whether the method of his appointment is legal or actual, the task entrusted to him in running the company requires eloquent care, dedication, honesty and giving priority to the company’s interest over his own. However, in view of the diversity and differences of management work from one company to another, it may result during the implementation of decisions in order to carry out the company’s activity some errors that would affect and destabilize the financial position of the company, and cause serious harm that leads to its bankruptcy, and thus the end of the life of the company. Hence, there is no room for the manager to bear civil responsibility, whether personally or jointly, as long as the company’s inability was due to his mistake. Hence, it is necessary to compensate the company for this danger that befell it, and the monetary compensation is included in the bankruptcy funds to pay the company’s debts, or the judgment is to pay the company’s debts by the manager directly. Punishment for his wrongdoing. He may also deviate his actions to characterize the act of the criminal legally, and consequently, criminal responsibility will result against him or against them in the case of polygamy, by approving a penal penalty for the course committed in the crime of bankruptcy by default or fraud - that is, the bankruptcy of the company in this case was not due to his civil error, but rather his bad faith in negligence and his intentionality in The commission of that act is the cause of the bankruptcy of the company under management. However, this acknowledgment of the responsibility and civil responsibility of the managers for the bankruptcy of commercial companies aims to apply legal protection to the company’s funds and to preserve its entity, except that it raises the question whether the path is legally protected from the arbitrariness of the company’s management structures. ................ ملخص المذكرة من خلال ما سبق دراسته ضمن موضوع المذكرة، نستنتج وأن المسير القائم بتسيير الشركة التجارية خاصة شركة الأموال كالشركة ذات المسؤولية المحدودة وشركة المساهمة. وسواء كانت طريقة تعيينه قانونية أو فعلية فإن المهمة التي أنيطت به في تسيير الشركة تقتضي الحرص البليغ والتفاني والأمانة وتغليب مصلحة الشركة على مصلحته الخاصة. إلا أنه ونظرا لتنوع واختلاف أعمال التسيير من شركة لأخرى، فإنه قد ينتج أثناء تنفيذ القرارات في سبيل القيام بنشاط الشركة بعض الأخطاء التي من شأنها أن تؤثر وتزعزع الوضع المالي للشركة، وترتب ضررا جسيما يؤدي إلى إفلاسها، وبالتالي انتهاء حياة الشركة ومن ثم فلا مجال لمناص المسير من تحمل المسؤولية المدنية سواء بصفة شخصية أو تضامنية وذلك طاما وأن عجز الشركة كان بسبب خطئه. ومن ثم يلزم بتعويض الشركة عن هذا الخطر الذي أحدق بها والتعويض النقدي يندرج ضمن أموال التفليسة لسداد ديون الشركة أو يكون الحكم بتسديد ديون الشركة من طرف المسير مباشرة. عقابا له على خطئه المسبب للضرر. كما أنه قد تحيد تصرفاته لتتصف بالفعل المجرم قانونا وبالتالي تترتب المسؤولية الجنائية ضده ، أو ضدهم في حالة التعدد وذلك بإقرار عقوبة جزائية للمسير المرتكب لجريمة الافلاس بالتقصير أو التدليس أي أن افلاس الشركة في هذه الحالة لم يكن لسبب خطئه المدني بل أن سوء نيته في الإهمال وتعمده في ارتكاب ذلك الفعل هو المتسبب في إفلاس الشركة محل التسيير. إلا أن هذا الإقرار للمسؤولية والمدنية للمسيرين عن إفلاس الشركات التجارية هدفه تطبيق الحماية القانونية لأموال الشركة وحفاظا على كيانها ، غلا أنه يطرح التساؤل هل أن المسير محميا قانونا من تعسف هياكل إدارة الشركة. .................... RÉSUMÉ DU MÉMORANDUM D’après ce qui a déjà été étudié dans l’objet du mémorandum, nous concluons que le cours des opérations de la société commerciale est en particulier la société monétaire telle que la société à responsabilité limitée et la société par actions. Que la méthode de sa nomination soit légale ou efficace, la tâche qui lui est confiée dans la conduite de l’entreprise exige beaucoup de diligence, de dévouement et d’honnêteté et l’intérêt de l’entreprise prévaut sur son propre intérêt. Cependant, en raison de la diversité et de la différenciation de l’activité d’exploitation d’une société à l’autre dans le cadre de la mise en œuvre des décisions afin d’exercer l’activité de la société peut produire certaines erreurs qui peuvent affecter et déstabiliser la situation financière de la société, La faillite de la société a été gravement endommagée et, par conséquent, à la fin de la vie de la société, il n’a pas été possible pour la société d’assumer la responsabilité civile, soit personnellement, soit solidairement, puisque l’incapacité de la société était due à sa faute. Par conséquent, la société est tenue de compenser ce risque et la compensation monétaire tombe dans les fonds de faillite pour payer les dettes de la société ou la décision de payer les dettes de la société directement par l’opérateur. Punition pour sa faute causant des dommages. Il peut également neutraliser ses actions afin de qualifier l’acte du contrevenant en tant que contrevenant légal et ainsi engager une responsabilité pénale contre lui. La faillite dans cette affaire n’a pas été causée par son erreur civile, mais par sa mauvaise intention de commettre un acte répréhensible délibéré et négligent. Toutefois, cette reconnaissance de la responsabilité et de la civilité des dirigeants pour la faillite des sociétés commerciales est destinée à appliquer la protection juridique des fonds de la société et à préserver son entité, mais soulève la question de savoir si le cours est légalement protégé contre l’arbitraire des structures de gestion de l’entreprise.